An algorithm for dynamic reconfiguration of mobile agents - Valente, Marco Tulio (2001)
In this paper we show an algorithm for dynamic reconfiguration of distributed applications based on the mobile agent model. We also show that the proposed algorithm can be easily implemented in the IPL language, a language with several abstractions for the construction of mobile applications in the Internet.